Youth, other ways of thinking, and the micro-geopolitics of knowledge between generations in the Secundarias Comunitarias Indígenas schools of Oaxaca, Mexico - Julieta Briseño Roa (Arizona State University, 2018)
In Oaxaca (Mexico), communality understood as a counter-hegemonic "thinking otherwise" permeated the indigenous teachers' movement, as it helped identify the existence of a geopolitics of knowledge as a strategy of modernity/coloniality. The present article offers ethnographically based evidence on the everyday construction of one of the community education projects: the model of the Secundarias Comunitarias Indígenas (SCI) of the state of Oaxaca, which was conceived as a project of epistemic emancipation. It contributes to the ongoing discussion on decolonizing (or decolonial) practices that might promote the construction of "ways of thinking otherwise" among young people, by analyzing the tensions that arise between two generations in practices that reveal two ways of conceiving indigenous education. Based on this analysis, the article discusses the relevance of the Educacion Intercultural Bilingüe model in Mexico for indigenous peoples is discussed.